2021
DOI: 10.1016/j.jns.2020.117257
|View full text |Cite
|
Sign up to set email alerts
|

Hypermetabolism is a reality in amyotrophic lateral sclerosis compared to healthy subjects

Abstract: Hypermetabolism (HM) in Amyotrophic lateral sclerosis (ALS) is the reflection of a high energy metabolic level, but this alteration seems controversial. The main objective of the study was to confirm the existence of HM during ALS compared to healthy subjects. Methods: A cohort of ALS patients was compared to a control group without metabolic disorder. The assessment included anthropometric criteria measurements, body composition by bioelectric impedance analysis and resting energy expenditure (REE) by indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…Defined as hypermetabolism, this phenomenon was subsequently confirmed, in a larger study, and was shown to be significantly increased by 14% and affected 62.3% of the 168 ALS patients (sex ratio M/F = 0.97) [105]. Data from the literature report that hypermetabolism affects up to 66% of ALS patients [104][105][106][107][108][109] and is an early event that persists throughout the course of disease [108,110,111]. Weight loss [112], hypermetabolism, and dyslipidemia are now considered as three major risk factors for ALS [107,109,113,114], and are associated with the severity of disease [108] (Figure 1).…”
Section: Discovery Of Hypermetabolismmentioning
confidence: 74%
“…Defined as hypermetabolism, this phenomenon was subsequently confirmed, in a larger study, and was shown to be significantly increased by 14% and affected 62.3% of the 168 ALS patients (sex ratio M/F = 0.97) [105]. Data from the literature report that hypermetabolism affects up to 66% of ALS patients [104][105][106][107][108][109] and is an early event that persists throughout the course of disease [108,110,111]. Weight loss [112], hypermetabolism, and dyslipidemia are now considered as three major risk factors for ALS [107,109,113,114], and are associated with the severity of disease [108] (Figure 1).…”
Section: Discovery Of Hypermetabolismmentioning
confidence: 74%
“…Despite a growing body of evidence linking metabolic alterations to disease outcome in ALS, interest in targeting metabolic dysfunction as a therapeutic approach has only grown in recent times (Fayemendy et al, 2021 ; Ferri & Coccurello, 2017 ; Ngo & Steyn, 2015 ). In this context, we aimed to evaluate the therapeutic potential of trimetazidine in the SOD1 G93A mouse model of ALS.…”
Section: Introductionmentioning
confidence: 99%
“…There is expanding evidence of multitudes of metabolic abnormalities in ALS (reviewed in [ 53 ]). Weight loss, which is not always attributable to dysphagia, is a common observation in patients [ 54 , 55 ], as is hypermetabolism, characterized by an increased basal metabolic rate [ 56 , 57 ]. It has been suggested that weight loss could occur if the increased energy expenditure in hypermetabolic patients is not balanced by an increase in dietary intake [ 58 ].…”
Section: Metabolism: a Brief Overviewmentioning
confidence: 99%